PERANCANGAN PROGRAM APLIKASI PERHITUNGAN NILAI RAPORT UNTUK SMA CANDRA NAYA - Natasha Angelica; Desi Arisandi; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The calculation of Candra Naya high school report score is still calculated using manual way, where the calculation is done one by one by the teacher. Doing the report score calculation in this way can lead to miscalculation and mistake while inputting the score of report. To reduce the risk of such errors, hence made a web-based report score distributed computing applications. This application was developed with the aim to simplify the process of data collection on Candra Naya High School students and staff and facilitate the counting of Candra Naya High School report cards. The application development is done by using the System Development Life Cycle method. Tools such as Adobe Dreamweaver CC2015, PHPMYAdmin, Microsoft Word, Microsoft Visio, and MYSQLWorkbench. This application is built using PHP programming language and SQL database. This application has been tested using User Acceptance Testing and Black Box Testing. This application can already be implemented in Candra Naya High School.